Effects of juniper removal and rainfall variation on tree transpiration in a semi‐arid karst: evidence of complex water storage dynamics. Issue 24 (16th August 2016) - Cardella Dammeyer, Heather; Schwinning, Susanne; Schwartz, Benjamin F.; Moore, Georgianne W.
Abstract: Brush removal is widely practiced as a tool for increasing groundwater recharge, but its efficacy depends greatly on the way in which the removed species interact with the hydrological system relative to the vegetation replacing it. We examined the effects of Ashe juniper removal in the recharge zone of the Edwards Aquifer, Texas, USA, a karst aquifer. The study was conducted in an Ashe juniper ( Juniperus ashei )–live oak ( Quercus fusiformis ) woodland on a hill slope composed of rocky, shallow soils over fractured limestone bedrock. Ashe juniper is a native species that has been encroaching grasslands and savannas over the past century. In September 2008, a plot was cleared of 90% of its juniper trees. Tree transpiration, predawn water potentials and vegetation cover across the cleared plot and an adjacent reference site were measured from May 2009 to December 2011. Stand‐level tree transpiration from May 2009 to March 2010 was diminished by a severe summer drought in 2009, from which trees were slow to recover. Subsequently, tree transpiration was 5–10× higher in the woodland compared to the clearing. For all of 2011, also a drought year, tree transpiration in the woodland exceeded precipitation inputs, indicating a high capacity for water storage at the study site. However, site differences for oak trees were generally larger than for juniper trees. While juniper removal accounted for a 431 mm year −1 difference in tree transpiration between sites, vegetation cover in the clearing increased from 42% to 90% over two years, suggesting that understory growth was increasingly compensating for the loss of juniper transpiration. We conclude that the removal of a relatively shallow‐rooted tree, when replaced with herbaceous vegetation and low shrubs, has little effect on deep recharge. By contrast, successive years of precipitation extremes may be more effective increasing recharge by lowering the water transport capacity of trees in the aftermath of severe drought. Copyright © 2016 John Wiley & Sons, Ltd.